THE ROLE OF NATURE-BASED DRAWING ACTIVITIES IN DEVELOPING AESTHETIC AWARENESS IN CHILDREN - Ismatova Mashhura Olimjon qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the importance of nature-based drawing activities in developing aesthetic awareness among children. It explores how observing and depicting natural objects, landscapes, and elements enhances children’s artistic perception, creativity, and sensitivity to beauty. The study highlights the effectiveness of hands-on activities such as sketching plants, animals, and natural scenery in fosteringvisual literacy, compositional understanding, and color perception. Findings suggest that integrating nature-inspired drawing into art education significantly strengthens children’s aesthetic consciousness and promotes holistic artistic development.